Case Study Of Trisakti Institute Of Tourism, Jakarta Total Quality Management Practice In Tourism And Hospitality Institute - Suzanto, Gatot Harry (2006)
The principle reason for the commencement of this topic were the great discrepancies between the realities of trying Total Quality Management (TQM) and the concepts of leadership and empowerment related to TQM in the literature.